Nascer no Brasil: continuity of care during pregnancy and postpartum period for women and newborns - Sonia Duarte de Azevedo Bittencourt; Elenice Machado Cunha; Rosa Maria Soares Madeira Domingues; Barbara Almeida Soares Dias; Marcos Augusto Bastos Dias; Jacqueline Alves Torres; Maria do Carmo Leal (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To estimate the adequacy of health care during pregnancy and the postpartum period in puerperal women and newborn users of the Unified Health System and verify the factors associated with greater adequacy. METHODS We used data obtained in the hospital interview, the prenatal card and the first telephone interview of 12,646 women participating in the study Nascer no Brasil (Birth in Brazil), conducted in 2011 and 2012. In the first stage of the analysis, the sociodemographic and obstetric characteristics of women and the estimation of adequacy of prenatal and postpartum care indicators are described. In the second stage, the cascade of care for actions related to puerperal women and their newborns is presented. Finally, maternal factors associated with the adequacy of the line of care are verified by means of multiple logistic regression. RESULTS Only two of the four prenatal indicators were considered satisfactory: initiation up to the 16th week of pregnancy and adequate number of appointments. The guidance on which maternity to go for delivery, as well as the guidance to perform the puerperal appointment and the performance of the heel prick test have reached partial level of adequacy. The puerperal appointment, the first routine appointment of the newborn and the obtaining of the heel prick test results presented unsatisfactory adequacy. In the joint analysis of indicators regarding the effective use of services, only 1.5% of mothers and their babies received all recommended health care. Multiparous women living in the North, Northeast and Midwest, with lower schooling, presented the lowest chances of continuity of care. CONCLUSIONS The indicators evaluated indicate that almost all women and their children presented partial and disjointed care, showing that the coordination of care is still a challenge in the health care of women and children in the puerperal pregnancy period.